Solution Of Order Batching Problem With Association Rules And Genetic Algorithm: A Case Study In Pharmacy Warehouse - Furkan Yener; Harun reşit Yazgan; Serap Ercan cömert; Sena Kır; Yağmur Kaya (Journal of Transportation and Logistics, 2016)
In this study, daily strategy of order picking is examined and proposed a new approach in a pharmacy warehouse. If the goods and orders are relatively small for the picker’s capacity, the order batching strategy should put to use. Daily orders was divided to order batches using mathematical model maximised the relationship among the orders. The order batches which are consist of more than one orders save up time and distance during the order picking period. Optimum solution of mathematical model take up time so that Genetic algorithm is used for order batching problem. Travelled the total distance is simulated in existing and batching strategy, the confidingness and performance of the results are tested statistically and argued in conclusion.